2019
DOI: 10.3389/fgene.2018.00684
|View full text |Cite
|
Sign up to set email alerts
|

Time- and Ventricular-Specific Expression Profiles of Genes Encoding Z-Disk Proteins in Pressure Overload Model of Left Ventricular Hypertrophy

Abstract: Mechanotransduction is an essential mechanism of transforming external mechanical stimulus to biochemical response. In cardiomyocytes mechanotransduction plays an important role in contraction, stretch sensing and homeostasis regulation. One of the major mechanosensitive area in cardiomyocytes, the Z-disk, consists of numbers of structural and signaling proteins, that may undergo conformational or gene expression changes under pathological stress conditions. In present study we examined a rat model of pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The Z-disk is a dense network of proteins anchoring thin filaments from opposing sarcomeres to actinins, titin, and many other structural and signaling proteins [38,39]. We observed a unique expression pattern in the genes coding for the proteins that assemble in this region, in which EDL exhibits lower expression levels compared to the psoas.…”
Section: Genes Associated With Sarcomere Z-disk Display a Unique Expr...mentioning
confidence: 86%
“…The Z-disk is a dense network of proteins anchoring thin filaments from opposing sarcomeres to actinins, titin, and many other structural and signaling proteins [38,39]. We observed a unique expression pattern in the genes coding for the proteins that assemble in this region, in which EDL exhibits lower expression levels compared to the psoas.…”
Section: Genes Associated With Sarcomere Z-disk Display a Unique Expr...mentioning
confidence: 86%
“…Interestingly, different heart compartments could also reveal distinct regional changes in Cmya5 gene expression following a disease-inducing intervention. Knyazeva et al [52] used a rodent model of pressure overload-induced heart disease and observed that Cmya5 mRNA levels declined in left ventricular samples 10 weeks following transverse aortic constriction (TAC), whereas the Cmya5 expression increased in right ventricular samples and remained unchanged in interventricular septum samples. In the same study, Fhl2 mRNA levels were not significantly altered, as it has also been shown previously in mice after TAC intervention [32].…”
Section: Discussionmentioning
confidence: 99%
“…many Dynein Axonemal Heavy Chain proteins were repressed after ZNF354C overexpression but due to their low expression pattern in the raw RNA-Seq data, these proteins were not further studied. Also genes relevant for the cardiovascular system were suppressed by ZNF354C: Cardiomyopathy Associated 5 (CMYA5) and Actinin Alpha 2 (ACTN2) are differentially expressed in the myocardium during progression of hypertrophy 25 . Loss of murine RGS5 reduces tumour angiogenesis 20 .…”
Section: Discussionmentioning
confidence: 99%